MANGOSTEEN SKIN EXTRACTS DECREASE THE ACTIVITY OF THE GAMMA-GLUTAMYLTRANSFERASE (ï§-GT) SERUM ON THE CIGARETTE EXPOSURE - Raharjo, Loo Hariyanto; Santoso, Hwa Tjeen Anna Lewi (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2014)
Exposure to cigarette smoke can cause oxidative stress, which characterized by increased activity of g-GT serum. The skins of the mangosteen (Garcinia mangostana L.) contain anthocyanins pigments, which can act as antioxidants to reduce free radicals. This study mainly aims to investigate the effect of mangosteen skin extracts to decreased activity of g-GT serum in rats exposed to cigarette smoke. This study was true experimental designs with randomized post-test only control group design. This study used thirty male rats were dividing into six treatment groups. Rats exposed to cigarette smoke, which came from two cigarettes, for 4 weeks lead to an increase free radicals in the body. The increased activity of g-GT serum to damp the free radicals. Mangosteen skin extracts can reduce free radicals so that the activity of g-GT serum decreased.The conclusion of this research is the mangosteen skin extracts can decrease the activity of the g-GT serum.